(untitled) (MSW Management Journal, 2026)
Background: The escalating global burden of carbapenem-resistant Klebsiella pneumoniae (CRKP) represents one of the most formidable challenges confrontingcontemporary clinical microbiology and infectious disease management. The dissemination of carbapenemase-encoding genes—including blaₙᴅᴹ, blaₒˣᴬ⁴⁸, and blaᴷᴘᴄ—across healthcare settings has severely curtailed therapeutic alternatives, resulting in elevated morbidity and mortality, particularly among critically ill andimmunocompromised patients.Objectives: To determine the prevalence of CRKP among clinical isolates recovered at a tertiary care hospital; to characterize the antimicrobial susceptibility profileof all K. pneumoniae isolates; to identify the distribution of carbapenemase-encoding resistance genes via molecular assays; and to correlate clinical and demographicvariables with resistance patterns.